Association between prealbumin levels and pulmonary hypertension in peritoneal dialysis patients: a single-center retrospective cohort study - Yakun Wang; Wuhua Jiang; Shoujun Bai; Yingchun Zhu; Xiansheng Miao; Xiaoyan Ma; Chong Zhang; Jiarui Xu (BMC Nephrology)
Abstract Background Pulmonary hypertension (PH) is common in peritonealdialysis (PD) patients and is associated with increased morbidity and mortality. However, the specific risk factors for PH and its prognostic impact remain underexplored, particularly in suburban populations. This study aimed to investigate the risk factors for PH and evaluate its impact on long-term all-cause and cardiovascular mortality in PD patients. Methods This single-center retrospective cohort study included adult patients who initiated PD and maintained it for at least three months at the Qingpu Branch of Zhongshan Hospital from January 2021 to December 2022. Baseline demographic, clinical, and laboratory data were collected. PH was defined as systolic pulmonary artery pressure ≥ 35 mmHg by echocardiography. Logistic regression models were used to analyze risk factors for PH, and survival outcomes were assessed using Kaplan-Meier analysis. Results Of the 103 PD patients included in the study, 29 (28.2%) were diagnosed with PH. Prealbumin levels were significantly lower in the PH group compared to the non-PH group (p = 0.007). Logistic regression analysis showed that higher prealbumin levels, whether treated as a standardized continuous variable (OR = 0.37, 95% CI: 0.18–0.76, p = 0.007) or categorized into tertiles, were consistently associated with a lower risk of PH. A significant trend across tertiles further supported this relationship (p-for-trend = 0.007). Patients with PH exhibited significantly higher all-cause mortality (31.0% vs. 6.8%, log-rank p < 0.001; HR = 5.70, 95% CI: 1.76–18.52) and cardiovascular mortality (20.7% vs. 2.7%, log-rank p < 0.001; HR = 14.94, 95% CI: 1.80–124.11). Conclusion PH is a significant predictor of all-cause and cardiovascular mortality in PD patients. These findings highlight the importance of identifying PH risk factors, particularly in suburban populations, to improve long-term outcomes in PD patients. Clinical trial number Not applicable.